2021
DOI: 10.1038/s41385-020-00342-x
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 inhibition promotes IFNγ- and NOS2-mediated control of Mycobacterium tuberculosis infection

Abstract: Mycobacterium tuberculosis (Mtb) infection induces pulmonary expression of the heme-degrading enzyme heme oxygenase-1 (HO-1). We have previously shown that pharmacological inhibition of HO-1 activity in experimental tuberculosis results in decreased bacterial loads and unexpectedly that this outcome depends on the presence of T lymphocytes. Here we extend these findings by demonstrating that IFNγ production by T lymphocytes and NOS2 expression underlie this T cell requirement and that HO-1 inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 57 publications
1
33
0
4
Order By: Relevance
“…Murine primers used: Actb F: 5’ AGC TGC GTT TTA CAC CCT TT 3’; Actb R: 5’ AAG CCA TGC CAA TGT TGT CT 3’; Il12b F: 5’ AGC ACC AGC TTC TTC ATC AGG 3’; Il12b R: 5’ GCG CTG GAT TCG AAC AAA G 3’. For flow cytometry, lung single cell suspensions were prepared as previously described ( Costa et al., 2020 ). For intracellular cytokine detection, prior to staining cells were incubated for 5 hours at 37°C with 10 µg/ml ESAT-6 1-20 or Ag85B 280-294 in the presence of brefeldin A and monensin during the whole 5h culture period, as previously published ( Sallin et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Murine primers used: Actb F: 5’ AGC TGC GTT TTA CAC CCT TT 3’; Actb R: 5’ AAG CCA TGC CAA TGT TGT CT 3’; Il12b F: 5’ AGC ACC AGC TTC TTC ATC AGG 3’; Il12b R: 5’ GCG CTG GAT TCG AAC AAA G 3’. For flow cytometry, lung single cell suspensions were prepared as previously described ( Costa et al., 2020 ). For intracellular cytokine detection, prior to staining cells were incubated for 5 hours at 37°C with 10 µg/ml ESAT-6 1-20 or Ag85B 280-294 in the presence of brefeldin A and monensin during the whole 5h culture period, as previously published ( Sallin et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…HO-1 exerts anti-inflammatory and cytoprotective effects, although the underlying mechanisms are not fully understood (196). Several studies have investigated the host beneficial or detrimental roles of HO-1 during TB infection (95,99,(192)(193)(194)(195). Andrade et al showed that active TB patients show a negative correlation between plasma levels of HO-1 and MMP-1 (95).…”
Section: Ho-1 Inhibitormentioning
confidence: 99%
“…Further, early secreted antigen ESAT-6-mediated nuclear translocation of transcription factor NRF-2 is required for Mtb-induced HO-1 expression (193). Recently, Costa et al discovered that HO-1 inhibition improves IFN-g-induced NOS2-dependent bacterial killing by murine macrophages (99). Additionally, HO-1 inhibition induced low intracellular non-protein bound iron in Mtb-infected macrophages and reduced iron deposition in the lungs of Mtb-infected mice (99).…”
Section: Ho-1 Inhibitormentioning
confidence: 99%
See 2 more Smart Citations